Analysis of Stock Investment Decisions in the Coal Mining Industry Sector in the LQ45 Index Using the Price Earning Ratio (PER) Method for the 2021-2023 Period - Albert Yansen; Rosita Yola Maylaningrum (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
Economic growth will always involve all aspects of life in Indonesia. Based on information from the Central Statistics Agency (2023), Indonesia recorded an economic growth of 5.31% in 2022. This figure is quite high compared to the 2021 achievement of only 3.70%. This study aims to analyze stock investment decisions in the coal mining industry sector in the LQ45 Index using the Price Earning Ratio (PER) method for the 2021-2023 period. The research methodology used is a quantitative descriptive method using secondary data obtained from the Indonesia Stock Exchange website to view the annual financial reports of mining companies. The objects of this study are the coal mining industry companies in the LQ45 Index for the 2021-2023 period, namely ADRO, ITMG, and PTBA shares. The analysis technique used is the Price Earning Ratio (PER) method. The results of this study from the 3 (three) sample companies used indicate that ADRO, ITMG, and PTBA shares are overvalued. ADRO shares have an intrinsic value of Rp. 2,380 and a market price of Rp. 2,430, ITMG shares with an intrinsic value of Rp. 25,650 and a market price of Rp. 26,700, and PTBA shares with an intrinsic value of Rp. 2,440 and a market price of Rp. 2,750 so that the investment decision that can be made for ADRO, ITMG, and PTBA shares is to sell the shares.